A selenium-catalysed para-amination of phenols. Issue 1 (December 2018) - Yan, Dingyuan; Wang, Guoqiang; Xiong, Feng; Sun, Wei-Yin; Shi, Zhuangzhi; Lu, Yi; Li, Shuhua; Zhao, Jing
Abstract Antioxidant enzyme glutathione peroxidase (GPx) decomposes hydroperoxides by utilizing the different redox chemistry of the selenium and sulfur. Here, we report a Se-catalysedpara -amination of phenols while, in contrast, the reactions with sulfur donors are stoichiometric. A catalytic amount of phenylselenyl bromide smoothly convertsN -aryloxyacetamides toN -acetylp -aminophenols. When thepara position was substituted (for example, with tyrosine), the dearomatization 4, 4-disubstituted cyclodienone products were obtained. A combination of experimental and computational studies was conducted and suggested the weaker Se−N bond plays a key role in the completion of the catalytic cycle. Our method extends the selenium-catalysed processes to the functionalisation of aromatic compounds. Finally, we demonstrated the mild nature of thepara -amination reaction by generating an AIEgen 2-(2′-hydroxyphenyl)benzothiazole (HBT) product in a fluorogenic fashion in a PBS buffer. Selenium has emerged as a metalloid for the catalytic construction of C–N bonds; however no functionalisation of aromatic compounds has been developed yet. Here, the authors report thepara -amination of phenols via two successive sigmatropic rearrangements of a redox versatile Se–N bond.